A Data Security Model for Improving the Privacy Cloud Computing - et. al., Pratibha Mundra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The category of services provided to clients, such as the storage of information systems, the network, and hardware, is cloud computing. Cloud storage can be accessed conveniently anywhere since the cloud operates remotely. The Cloud provider uses the computing service. Data in the cloud is not safe since private data can be accessed by an unauthorized user. Therefore, it uses a distinct encryption method to secure the data to provide data protection. This paper explores data protection in cloud computing. It is the analysis of data in the cloud & aspects of safety-relevant to it. In this research, we have used two data encryption and decryption techniques for a better result than the previous research work which had some limitations. This algorithm is faster and more robust than that of the RSA-BlowFish.